The significance of the Russian Orthodox diaspora and its effect on the Christian west - Zernov, Nikolaj Michajlovič (Studies in church history, 1976)
The enforced emigrations caused by political or religious conflicts have often been an enriching and stimulating factor in the cultural history of mankind.Lenin’s dictatorship based on red terror forced more than a million Russians to flee from their own country and settle down in various parts of the world. The Russian diaspora included a great variety of people, among them many well-known men. It will suffice to mention a few names: Ivan Bunin (1870-1953), Dimitry Merezhkovsky (1865-1941) in literature; Sergy Rachmaninov (1873-1943) and Igor Stravinsky (1882-1971) in music; Vasily Kandinsky (1866-1944) in painting; Fedor Chaliapin (1873-1938) and Anna Pavlova (1881-1931) in the theatre; Mikhail Rostovtsev (1870-1952) and Georgy Vernadsky (1887-1973) in history; Igor Sikorsky (1889-1972) in aviation; Nikolay Menschokov (b. 1900) in geology. All these people made a substantial contribution to the contemporary world of art and learning.